1980
DOI: 10.1080/03601238009372160
|View full text |Cite
|
Sign up to set email alerts
|

Nature of N‐S bond cleavage of 2,3‐dihydro‐2,2‐dimethyl‐7‐benzofuranyl (di‐n‐butylaminosulfenyl) (methyl)carbamate

Abstract: The cleavage of the N-S bond in 2,3-dihydro-2,2-dimethyl-7-benzofuranyl (di-n-butylaminosulfenyl) (methyl)carbamate was examined in different buffer solutions (hydrolysis), in buffer solution containing sulfhydryl reagents (thiolysis) and on thin-layer chromatographic plates. In buffer solution and on thin-layer plates, N-S bond cleavage readily occurred to give carbofuran as a major product, with minor amounts of bis-carbofuran-N,N'-disulfide and -trisulfide. The hydrolysis reaction in buffer proceeded with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Carbosulfan was not detected in the different parts of the stem, except in some low-weight Douglas firs. As Umetsu et al (1980) reported high rates of decomposition of carbosulfan into carbofuran under acidic conditions, a study was conducted on the root system of plants sampled on the field site (pH of the soil, 5.5). Roots were washed with water, prepared, and analyzed as previously described for the stems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbosulfan was not detected in the different parts of the stem, except in some low-weight Douglas firs. As Umetsu et al (1980) reported high rates of decomposition of carbosulfan into carbofuran under acidic conditions, a study was conducted on the root system of plants sampled on the field site (pH of the soil, 5.5). Roots were washed with water, prepared, and analyzed as previously described for the stems.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in carbofuran concentration may be due a metabolic pathway of carbofuran, which cannot be the same as for a "one-dose" application since the plant is in constant contact with the carbosulfan-carbofuran complex. The age of the plant may also affect the way the plant responds to the presence of these insecticides and changes the metabolic pathways proposed by Umetsu et al (1980) and by Free and Saunders (1973).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid N-S(II) reactivity toward cellular thiols is the basis of the mechanism of action of many antibiotics (Turos et al, 2002;Turos, 2005;Revell et al, 2007;Prosen et al, 2011;Ramaraju et al, 2012;Shang et al, 2013), pesticides (Chiu et al, 1975;Umetsu et al, 1980;Fukuto et al, 1983;Wallace and Zerba, 1989), and prodrug candidates (Olbe et al, 2003;Hemenway, 2006;Hemenway et al, 2007;Nti-Addae, 2008;Proença et al, 2011;Huttunen et al, 2012). Similarly, the reactivity of N-S(II) compounds to other common functional groups found in the cell (other than thiols) is not detected, showing that the main reactivity of N-S(II) compounds in the cellular environment comes from -SH groups and not from others (alcohols, amines, carboxylic acids, etc.)…”
Section: Literature Review On N-s-thiol Reactivitymentioning
confidence: 99%
“…At all doses on all species tested, either by contact or by the systemic route, it had activity similar to that of carbofuran. This derivative retains the biological activity of the parent compound which is liberated in the insect after enzymatic cleavage of the N-S bond (Umetsu et al, 1980).…”
Section: R -N(ch~)-chz-chz-ohmentioning
confidence: 99%